Representations of Chagas disease among Bolivian immigrants in the city of São Paulo - Silveira, Cássio; Forsyth, Colin; Junior, Nivaldo Carneiro; Goldberg, Alejandro; da Silva, Lia Maria Britto; da Silva, Rubens Antonio; Shikanai-Yasuda, Maria Aparecida (Frontiers in Tropical Diseases, 2024)
BackgroundTransnational immigrants are particularly impacted by neglected diseases, which take a heavy biological, social, and emotional toll in these marginalized communities. Chagas disease has transformed from an exclusively rural to an increasingly urban phenomenon encompassing non-endemic areas in Latin America.MethodsThrough semi-structured interviews, we investigated representations of Chagas disease in Bolivian immigrants in São Paulo, Brazil. Between August and September 2015, 27 adult migrants were interviewed, 11 of them with Chagas disease. We explored problems of access to health services and essential knowledge about the disease, as well as related conceptions and health practices.ResultsParticipants constructed social representations of Chagas through interactions with family and social networks, drawing on earlier experiences in Bolivia. Diagnosis often provoked fear, and participants faced barriers to care based on language differences and uncertainties about the disease and treatment options. Healthcare personnel played an important role in alleviating concerns and facilitating access to information.DiscussionThe complex intersection of migration and neglected diseases creates challenges for local and national health programs, requiring innovative responses incorporating the perspectives and needs of the often vulnerable affected communities.